The Effects Of Mixing And Curing On Morphological And Mechanical Properties Of Epoxy-Albasia Composites - Pratiwi, Henny (SENATIK STT Adisutjipto, 2016)
This research is aimed to know the effect of mixing time, mixing speed and curing temperature on morphological and mechanical properties of epoxy-albasia wood fiber composites. The method used in the manufacturing process was hand lay-up method. The fibers with 30 mesh and 25% volume fraction are mixed with epoxy for the time variations of 15 and 45 minutes by speed variation of 695 rpm, 773 rpm, and 853 rpm. In order to investigate the effects of curing temperature, the same mixture was blended manually for 20 minutes and cured with the temperature variation of 40, 50, 60, 70 and 800C. Experimental results show that mixing the fiber and matrix with the speed of 695 rpm for 15 minutes increases the tensile strength but slightly declines the impact strength. This phenomenon could be possibly caused by the longer the mixing time, the higher the amount of foreign particles entered into the mixture that could affect its properties. Both the tensile and impact tests show that the temperature of 80oC is the optimum curing temperature for epoxy-albasia wood fiber composites. Crack deﬂection presented by Scanning Electron Microscopy (SEM) micrographs results in an increase in the crack propagation path and in the energy-dissipating events in the region immediately ahead of the crack tip.